Comparative study of ZnCl2‐activated and steam‐activated carbons used in the anode of microbial fuel cells. Issue 2 (12th December 2019) - Nguyen, Dang‐Trang; Taguchi, Kozo
Abstract: The anode electrode plays a vital role in the performance of microbial fuel cells (MFCs) because it has the function of collecting electrons generated by microorganisms living in the anode chamber. In this letter, activated carbon papers fabricated based on ZnCl2 ‐activated carbon (ZAC) or steam‐activated carbon (SAC) were used as the anodic materials. Escherichia coli was used as an electrogenic bacterium in a two‐chamber MFC. This study compared the performance of ZAC and SAC in the anode. X concentrations (X = 10, 20, and 40 wt%) of ZAC or SAC in the anodes were investigated. The ZAC‐based anode outperformed the SAC‐based anode in terms of MFC‐generated power density. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.